(untitled) (Analysis in Theory and Applications, 2011)
In the present paper we study properties of Szász-Durrmeyer operators. These operators are introduced in [5] and generalize the integral operators proposed by S. M. Mazhar and V. Totik in [12]. We also generalize some results obtained by M. Heilmann[6] and D.-X. Zhou[16].